PENINGKATAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DENGAN MODEL JIGSAW KELAS XII SMK NEGERI 4 BONDOWOSO - SUMARTONO SUMARTONO (ACTION : Jurnal Inovasi Penelitian Tindakan Kelas dan Sekolah, 2023)
Islamic Religious Education so far tends to use monotonous methods and approaches so that the learning process is less interesting and less active. The results of this study answered various problems regarding teacher and student activities in the learning process of Islamic Religious Education through the application of a jigsaw in class XII Nursing Assistant 1 at SMK Negeri 4 Bondowoso, as well as improving student learning outcomes. This research is in the form of Classroom Action Research (CAR). The research was conducted in two cycles and four stages of implementation; planning, action, observation and reflection. Data collection by observation, test and documentation. The results showed that the jigsaw method of learning Islamic Religious Education on the subject of the obligation to worship and give thanks to Allah SWT improves the learning outcomes of class XII students of Nursing Assistant 1 even semester of the 2022/2023 academic year. The successful application of the jigsaw method is known from the increase in student learning outcomes in cycle I, teacher activity gets an average score of 2.50 in the pretty good category, student activities get an average score of 3.00 in the good category and student learning outcomes get a completeness score of 75% with incomplete value 25%. In cycle II teacher activities got an average score of 3.00 in the good category, student activities got an average score of 3.60 in the very good category and student learning outcomes obtained a completeness score of 90% with an incomplete score of 10%. Students are more active and skilled in the learning process. Teachers are more skilled, varied in teaching activities, use of methods. In conclusion, the jigsaw model can improve student learning outcomes in Islamic Religious Education subject on the obligation to worship and give thanks to Allah SWT. ABSTRAKPendidikan Agama Islam selama ini cenderung menggunakan metode dan pendekatan yang monoton sehingga proses pembelajaran kurang menarik dan kurang aktif. Hasil penelitian ini menjawab berbagai masalah tentang aktivitas guru dan siswa dalam proses pembelajaran Pendidikan Agama Islam melalui penerapan jigsaw di kelas XII Asisten Keperawatan 1 SMK Negeri 4 Bondowoso, serta peningkatan hasil belajar siswa. Penelitian ini berbentuk Penelitian Tindakan Kelas (PTK). Penelitian dilakukan dengan dua siklus dan empat tahap pelaksanaan; perencanaan, tindakan, observasi dan refleksi. Pengumpulan data dengan observasi, tes dan dokumentasi. Hasil penelitian menunjukkan bahwa metode jigsaw pembelajaran Pendidikan Agama Islam pada materi kewajiban beribadah dan bersyukur kepada Allah SWT meningkatkan hasil belajar siswa kelas XII Asisten Keperawatan 1 semester genap tahun pelajaran 2022/2023. Berhasilnya penerapan metode jigsaw diketahui dari adanya peningkatan hasil belajar siswa pada siklus I, aktivitas guru mendapat nilai rata rata 2,50 dengan kategori cukup baik, aktivitas siswa mendapat nilai rata 3,00 dengan kategori baik dan hasil belajar siswa memperoleh nilai ketuntasan 75% dengan nilai tidak tuntas 25%. Pada siklus II aktivitas guru mendapat nilai rata rata 3,00 dengan kategori baik, aktivitas siswa mendapat nilai rata 3,60 dengan kategori sangat baik dan hasil belajar siswa memperoleh nilai ketuntasan 90% dengan nilai tidak tuntas 10%. Siswa lebih aktif dan terampil dalam proses pembelajaran. Guru lebih terampil, variatif dalam kegiatan mengajar, penggunaan metode. Kesimpulannya model jigsaw dapat meningkatkan hasil belajar siswa mata pelajaran Pendidikan Agama Islam materi kewajiban beribadah dan bersyukur kepada Allah SWT.